Caregiver perspectives on barriers and facilitators to primary care for autistic adults: A qualitative study - Stein Duker, Leah I.; Goodman, Elizabeth; Pomponio Davidson, Amber; Mosqueda, Laura (Frontiers in Medicine, 2022)
Background: Primary care is associated with greater access to healthcare services and improved health outcomes. However, autistic adults report challenges accessing and utilizing primary care, in addition to unmet healthcare needs. The need to minimize existing barriers and identify strategies to facilitate successful healthcare encounters is increasingly important as autistic adults represent a growing segment of society. Minimal research has examined primary healthcare encounters for this population. Methods: As part of a larger convergent parallel design mixed-methods study that recruited autistic adults, caregivers of autistic adults, and primary care providers treating autistic adults, interviews were conducted with 31 caregivers of autistic adults. Caregivers were predominantly female (94%), and the autistic adult they cared for were primarily male (87%), with a mean age of 24 years. Thematic analysis was employed to elucidate the barriers to care, suggestions to mitigate challenges, and/or successful strategies implemented during care encounters for autistic adults, as reported by their caregivers. Results: Reported here are the results only from the caregiver interviews, in which sSeven themes emerged: (1) finding a primary care provider; (2) patient-provider communication; (3) anxiety due to unpredictability, an overstimulating sensory environment, and waiting time; (4) participation of consumers in the healthcare process; (5) stigma and assumptions about autism; (6) caregiver experiences; and (7) the impact of culture and ethnicity on care. Conclusion: Findings from this study have the potential to inform the development of, or improve existing, client-centered interventions to improve primary healthcare services for autistic adults.